Chagas disease pharmacotherapy and its chemical structure activity relationship - Scarim, Cauê Benito [UNESP]; Chiba, Diego Eidy [UNESP]; Bosquesi, Priscila Longhin [UNESP]; dos Santos, Jean Leandro [UNESP]; Chin, Chung Man [UNESP] (My University, 2017)
Therapeutic arsenal currently available for Chagas disease is restricted in only two drugs, nifurtimox and benznidazole, since 1960s and 1970s, respectively. Despite the efforts to develop new drugs, until now, no new drugs were approved. This chapter describes the history of the two drugs used, as well as their mechanism of action, toxicity and relation-structure activity (SAR). In addition, the chapter addresses new therapies in clinical research, and those which are involved in programs (consortia) to develop new treatments for Chagas' disease.
Keywords: Action mechanism; Benznidazole; Chagas' disease; Nufurtimox; Structure activity relationship; T. cruzi